Correction to: Quality of life after laparoscopic hysterectomy versus abdominal hysterectomy - Yasushi Kotani; Kosuke Murakami; Risa Fujishima; Akiko Kanto; Hisamitsu Takaya; Masao Shimaoka; Hidekatsu Nakai; Noriomi Matsumura (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.